2002
DOI: 10.1523/jneurosci.22-02-00428.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mutation ofDrosophila homerDisrupts Control of Locomotor Activity and Behavioral Plasticity

Abstract: Homer proteins have been proposed to play a role in synaptogenesis, synapse function, receptor trafficking, and axon pathfinding. Here we report the isolation and characterization of the Drosophila gene homer, the single Homer-related gene in fly. Using anti-Homer antibody we show that Homer is expressed in a broad range of tissues but is highly enriched in the CNS. Similarly to its mammalian counterpart, the Drosophila Homer localizes to the dendrites and the endoplasmic reticulum (ER). This subcellular distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 53 publications
2
70
0
Order By: Relevance
“…Male flies react to olfactory, visual, and tactile signals with a complex and strong courtship toward females, and this behavior can be conditioned by previous experience. As compared with wild-type flies, homer R102 mutants were lacking behavioral plasticity and failed to form and/or retain the conditioning by the nonreceptive mated female (7). In addition, homer R102 -mutant flies exhibited higher levels of spontaneous locomotor activity.…”
Section: Animal Behaviormentioning
confidence: 94%
See 2 more Smart Citations
“…Male flies react to olfactory, visual, and tactile signals with a complex and strong courtship toward females, and this behavior can be conditioned by previous experience. As compared with wild-type flies, homer R102 mutants were lacking behavioral plasticity and failed to form and/or retain the conditioning by the nonreceptive mated female (7). In addition, homer R102 -mutant flies exhibited higher levels of spontaneous locomotor activity.…”
Section: Animal Behaviormentioning
confidence: 94%
“…A total of 12 Homer cDNAs have been cloned from rat, mouse (5,6), Drosophila (7), and human brains (6). Proteins encoded by these cDNAs share a similar structure and are splice variants of three independent mammalian genes (homer-1, 2, and 3) and of one Drosophila gene (D-homer).…”
Section: The Homer Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Drosophila Homer (D. Homer) is highly homologous to mammalian Homer1 proteins [261] and recent behavioral screens for Drosophila mutants revealed that Drosophila lacking Homer (homer R102 ) exhibit increased sensitivity to the acute sedative effects of alcohol and fail to develop normal levels of rapid tolerance upon a subsequent alcohol exposure. In support of an active role for Homer in regulating alcohol sensitivity, pan-neuronal expression of WT Homer reduced their initial sensitivity to acute alcohol and restored the development of rapid tolerance [260].…”
Section: Homers and Alcohol-induced Neuroplasticitymentioning
confidence: 99%
“…However, more accurate identification and mapping of novel neuronal circuits has been hampered by the lack of a genetically encoded and phenotypically neutral dendritic marker. Over the years, many such markers have been proposed and several were recently examined (12), namely MAP2 (13,14), Nod::YFP (4, 15-18), Homer::GFP (19), and DSCAM17.1::GFP (20,21). The analysis of these markers reveals that none of them labels the entire somatodendritic field.…”
mentioning
confidence: 99%